Strategies for National Transformation: From Developing to Developed - Mujuranto Sihotang; Marsono Marsel Sihotang; Demita Sihotang; Stiglitz Ernst; Jose Lemos Freitas (Intitute of Computer Science (IOCS), 2023)
The process of national transformation from developing to developed status is a complex endeavor that requires addressing multidimensional challenges while capitalizing on strategic opportunities. This research investigates the challenges faced by developing countries in their transformation journey, identifies effective strategies for achieving successful transformation, and explores the implications for policy formulation. Multidimensional challenges encompassing political instability, economic disparities, inadequate education and healthcare, environmental degradation, and gender inequality are analyzed in their interconnectedness. Effective transformation strategies encompass human capital development, economic diversification, governance reforms, sustainability integration, trade promotion, social inclusion, innovation, and international collaboration. The research draws insights from successful transformation case studies, including South Korea, Singapore, China, and others, highlighting the role of visionary leadership, strategic investments, and adaptability to global dynamics. Policy implications emphasize holistic approaches, good governance, investment in education and infrastructure, economic diversification, social equity, and climate resilience. The research identifies areas for further exploration, including long-term impact assessments, context-specific strategies, sustainable development metrics, gender equality, and behavioral economics. In conclusion, this research contributes a comprehensive understanding of the challenges, strategies, and implications involved in national transformation, guiding governments, international organizations, and stakeholders toward sustainable and equitable development paths